The Impact of COVID-19-Induced Changes at Schools on Elementary Students' School Engagement - Thorsteinsen, Kjærsti; Parks-Stamm, Elizabeth J.; Olsen, Marte; Kvalø, Marie; Martiny, Sarah E. (Frontiers in Psychology, 2021)
In spring 2020, the COVID-19 pandemic led to the shutdown of schools in many countries. Emerging research documents the negative effects of the pandemic and particularly of the shutdown of schools on children’s well-being. The present research extends this research by investigating how structural changes made in schools upon reopening to align with COVID-19 restrictions were related to children’s emotional school engagement and subjective well-being. An online questionnaire with elementary school children and their parents conducted in Norway in June 2020 (N = 93 parent-child dyads; 46 boys, 47 girls; mean age children = 9.70 years, SD = 1.81) assessed structural changes in schools and children’s coping with these changes, emotional school engagement, subjective well-being, self-reported performance in school, and demographics. Results showed that neither receiving a new teacher nor being assigned to a new (smaller) group were associated with negative outcomes. However, children who did not like their new group showed reduced emotional school engagement and subjective well-being, indicating that specific students particularly suffered from the pandemic-induced restrictions. The relationship between liking one’s group and subjective well-being was mediated by emotional school engagement. Applied and theoretical implications are discussed.